Supervised teaching practice in physical education: The mobilization of teacher knowledges - de Carvalho, Taynara Franco [UNESP] (2019)
This work focuses on the training of physical education teachers in the Supervised Teaching Practice. It aims to understand the knowledges that are mobilized in the Supervised Teaching Practice. The qualitative research, descriptive study, using as techniques: interview with 10 trainees and seven teachers and content analysis. The participants pointed out that the construction of the knowledges and the rescue of the experiences are continuous, having as influences the schooling, the teaching practice and the training courses. The mobilization of the disciplinary, curriculum, pedagogical tradition and pedagogical action knowledges by students in the internship occurred according to the needs and challenges of this process, forming a kind of reservoir. From this reservoir of knowledges, teachers mobilize the experiential knowledge (an amalgam of knowledges) in the supervision and guidance of the internship. In this knowledge base, the teacher is supplied, while the student is guided in the practice of teaching.